Self‐made microextraction by packed sorbent device for the cleanup of polychlorinated biphenyls from bovine serum. Issue 8 (29th March 2016) - Yang, Liu; Han, Qiang; Cao, Shuya; Yang, Junchao; Zhao, Jiang; Qin, Molin; Ding, Mingyu
Abstract : Microextraction by packed sorbent, a miniaturized form of the solid‐phase extraction, is a new sample pretreatment technology mainly used for bioanalysis. In this work, self‐made device was fabricated by packing C18 sorbent into a microinjection needle (50 μL) and then applied for the analysis of polychlorinated biphenyls in bovine serum followed by gas chromatography with mass spectrometry determination. Compared with conventional solid‐phase extraction, the developed method bears many intriguing properties such as low consumption of the sample and organic solvent, time‐saving and easy operation, which are of great interest and desire for bioanalysis applications. A series of parameters that affect the analytical performance, such as the type of elution, the aspirating/dispensing cycles of sample loading and elution, washing solution, and matrix effects, was investigated in detail. Under the optimized conditions, the proposed method presented a good linearity ( R ≥ 0.986) and satisfactory sensitivity and limits of detection (0.06–0.53 ng/mL) and quantification (0.20–1.77 ng/mL), respectively. In addition, satisfactory recoveries (60.0–91.4%) and accuracy (RSD ≤ 5.72%) were achieved after optimizing the conditions when applying the developed method to real sample analysis. The screening of polychlorinated biphenyls residues in bovine serum samples by the developed method demonstrated that the assay is ideally suited as a monitoring method for polychlorinated biphenyls residues in bioanalysis.